Mechanical Smoke Exhaust in Underground Transport Passage of Hydropower Station - Angui Li; Yeqiu Wu; Jiangyan Ma; Ran Gao; Jiang Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper, the fire scenario occuring in the main transformer hall of an underground hydropower station is taken as an example of the mechanical smoke exhaust effect in the transport passage when the smoke spilled from the fired main transformer hall is analyzed by means of theoretical analysis, experiment and FDS simulation. Firstly, the mathematic correlations regarding the mechanical exhaust rate are derived through theoretical analysis. Secondly, a series of experiments are conducted to investigate the smoke spreading in the transport passage under different mechanical exhaust rates, and the same smoke spreading processes are simulated using FDS. By comparing the results of theoretical analysis, experiments and FDS simulations, it is showed that the mechanical exhaust rate prescribed in the regulation of China is adequate for the transport passage of main transformer under a main transformer hall fire. DOI:http://dx.doi.org/10.11591/telkomnika.v10i5.1269